Regional Societies: Fostering Competitive Research Through Virtual Infrastructures - Jennings, Steven F (Public Library of Science, 2004)
The MidSouth Computational Biology and Bioinformatics Society (MCBIOS) describes its efforts to provide local opportunities for researchers to learn and connect with colleagues